Impact of the Significant Financial Potential Factors on the Economic Development of the Region - Anastasiya Koshevarova; Burova Ekaterina; Svetlana Suloeva; Kseniya Kozhina; Guljakhon Makhmudova (International Journal of Technology)
Financial potential is an important indicator that reflects the availability of resources and opportunities for the development of a region. A comprehensive study of this indicator is very necessary to achieve growth and improve the financial and economic climate in any country and region. Therefore, this study aimed to identify statistically significant factors of financial capacity that affect economic growth and financial potential. In order to achieve the stated objectives, regression analysis was adopted and the study sample comprised data obtained from 82 regions of Russia. It is also important to comprehend that this study spanned the period from 2009 to 2022. Three models were examined, namely Fixed Effects Model (FEM), Ordinary Least Squares (OLS), and Random Effects Model (REM), and FEM was identified as more precise for the study analysis. The results showed nine very important factors with the capability to influence financial potential. These factors include budget (coefficient of covering budget expenses with own income, external financing ratio), investment (investment in fixed assets per capita, financial performance ratio of organizations per capita), credit (level of debt load of corporations, level of debt load of individuals; loans to deposit ratio), and household financial performance (consumer spending per capita), all of which were identified at a 99% confidence level. Accordingly, all factors, except the loan-to-deposit ratio, were observed to be positively correlated with indicators of socio-economic development (GRP per capita) and financial potential.